Caracterização das cinzas de incineração de resíduos industriais e de serviços de saúde - Silva,Maristela Lopes (2008)
Three ash samples from an incinerator in Belo Horizonte (Brazil) were physically and chemically characterized. The chemical composition of the ashes was not always the same, neither in terms of the chemical species nor in terms of the quantities of those that are common to the three ashes. The ashes called CF1 and CF3D contain heavy metals above the detection limits of the analytical methods and the zinc concentration is high enough to justify treatment of the ashes. For these ashes, a high loss on ignition was found, indicating that the process of incineration might present failures.